Lesley K. Twomey, The Sacred Space of the Virgin Mary in Medieval Hispanic Literature from Gonzalo de Berceo to Ambrosio Montesino - Ana Elvira Vilchis Barrera (Medievalia)
Lesley K. Twomey, The Sacred Space of the Virgin Mary in Medieval Hispanic Literature from Gonzalo de Berceo to Ambrosio Montesino, Woodbridge: Tamesis, 2019, 484 pp.